Research Progress of Ponticulus Posticus: A Narrative Literature Review - Xu, Xiaoyan; Zhu, Yuefeng; Ding, Xing; Yin, Mengchen; Mo, Wen; Ma, Junming (Frontiers in Surgery, 2022)
Objective: The purpose of this review was to consolidate the current literature related to ponticulus posticus (PP) and improve the systematic understanding of this anatomical variant of atlas among spine surgeons. Methods: Articles reviewed were searched in PubMed, Ovid MEDLINE, and EMBASE using search terms: (“ponticulus posticus” or “posticus ponticus” or “foramen arcuate” or “foramen arcuale” or “foramen sagittale” or “foramen atlantoideum posterior” or “Kimmerle’s anomaly” or “foramen retroarticulare superior” or “canalis vertebralis” or “retroarticular vertebral artery ring” or “retroarticular canal” or “retrocondylar vertebral artery”). All articles of any study design discussing on PP were considered for inclusion. Two independent authors read article titles, abstracts and the included appropriate articles. The relevant articles were studied in full text. Results: A total of 113 literatures were reviewed and consolidated in this narrative review. These articles are roughly divided into the following five subcategories: (1) epidemiology, (2) pathology and anatomy, (3) clinical presentation, (4) surgical significance, (5) radiographic examination Conclusion: PP was nonnegligible with a high prevalence. PP compressed the V3 segment of the artery, the suboccipital nerve and the venous plexus, consequently contributing to the incidence of neurological pathologies. When a PP was observed or suspected on a lateral radiograph, we recommend that a CT scan of a patient who is about to receive a C1LMS should be performed, which could determine a safe entry point and a right trajectory of screw insertion.